Using Generated Artificial Intelligence (AI) Educational Tools for Enhancing Classroom Teaching Efficiency - Mohamed Edali; Hanadi Saad; Ali Elkamel (African Journal of Advanced Pure and Applied Sciences, 2024)
ChatGPT is a language model (LLM) dependent text-generating artificial intelligence (AI). These LLMs are trained by being fed copious amounts of data to pick up statistical regularities which they then use, like a game of darts where they try to predict what word or action is most likely next and where it came from, without looking at pre-existing solutions or simply copying responses precisely. Considering the vast scope of tasks that can be automated reasonably well with such techniques, generative AI seems to mark another stride forward in this direction. Typically, some of the spots at the forefront of technology and creative sectors are those most vulnerable to automation. Like every other field, artificial intelligence too has had a monumental impact on educational setups. With AI developments, the teaching staff can avail themselves of many tools that make student learning more effective while also making teaching easier. Let us therefore concentrate in this article on the best AI tools for educators. These will transform pedagogy into an exciting process where imparting knowledge is easy and effective and will have a significant impact on the teaching profession. Such methodologies exploit artificial intelligence algorithms to escalate engagement, customization, and productivity in education, resulting in more inventive and inclusive areas for learning. In this regard, it is important to note that developers should carefully consider dangers that could be posed by distortions such as bias, low-quality information, and learner isolation.